Agribusiness strategy and rural development: A case study of Ihunga Sub County, Ntungamo District - Denis, Simpson Singahache (Kabale University, 2022)
The purpose of the study was to investigate the relationship between agribusiness strategy and rural development in Ihunga Sub county, Ntungamo District. Case study research design was used and this allowed the researcher to concentrate on selected households and identified various interactive processes at work. A sample of 395 respondents from 30,000 target population participated in the study by answering the questionnaire and took part in interviews. Data collected by the researcher was entered using Statistical Package for Social Scientists (SPSS), and descriptive statistics analysed. and the researcher interpreted the data from the socio-demographic characteristics of the study respondents using frequencies and percentages to show the distribution of respondents on different items. The study was guided by three objectives; namely: (i) To establish how agribusiness strategy contributes to rural development. (ii) To examine the challenges hindering agribusiness strategies in rural development. (iii) To analyse the mitigation measures to the challenges hindering agribusiness strategy towards rural development in Ihunga Sub County, Ntungamo District. The key study findings were: lack of provision of food security strategy, poor policy articulation and lack of supply of agricultural inputs to farmers. The conclusion of the study was that agribusiness strategy has a prominent role to play in advancing rural development in Ihunga Sub County, Ntungamo District. Basing on the study objectives and subsequent findings, the study recommended among others: to have food security in homes and families using agribusiness strategy for developments; to launch cooperative societies so that agro-based producers with common goals advance their aim to kick poverty out of their areas by setting up the bargaining power to look for market, reliable technology and inputs to boost their operations aiming at developing their rural area; to adopt agribusiness strategy for rural development and widening employment opportunities; Government to come in and enforce policies and laws aiming at regulating birth so as to control population growth, Government should come in to properly articulate policies and ensure their effective implementation to enhance rural development basing on agribusiness strategy as the benchmark and the Ugandan government to prioritize the agriculture sectors by allocating a big proportion of the budget to agriculture and industry sectors.